Utilization of the heat-treated silicate rocks in the cement and cement slurry manufacturing - Мазурок, Павло Степанович; Буюн, Маргарита Володимирівна; Токарчук, Володимир Володимирович; Свідерський, Валентин Анатолійович (Technology audit and production reserves, 2016)
Reliable operation of oil and gas wells depends largely on the quality of cementing. Currently lightweight cements with large water-cement ratio are used. To improve the properties of cement slurries we can use fine lightweight additives with the components, which are capable of reacting with the hydration products of clinker component to produce additional amounts of calcium hydrosilicates. An influence of the natural and heat-treated silicate rocks on the properties of cement and cement slurries is studied. It is found that the heat-treated silicate materials have a positive impact on the strength of cements and cement slurries. Research results show that strength of the samples, which contained heat-treated additives, higher than strength of the samples, which contain a corresponding amount of natural additives, at all concentrations of additives and all hardening time. The increased strength of cements and cement slurries based on heat-treated materials is provided, first of all, by reactive decomposition products of clay minerals. During the heat treatment of materials is not only the initial decomposition of minerals, but also the formation of new ones. However, this does not lead to deterioration in the rheological properties of cement slurries. Feasibility of using heat-treated silicate rocks as facilitating additives in the production of cements and cement slurries is confirmed under the conditions of factory laboratory. Cement slurry based on heat-treated kaolin clay meet regulatory requirements for such materials. Values of water separation, setting time, thickening time and bending strength are almost identical within the control bentonite clay-based sample, and the strength of cement slurry at the age of 180 days with the heat-treated additive nearly in 1,5 times higher.